2016
DOI: 10.1200/jco.2015.62.3314
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk in Childhood Cancer Survivors Without a History of Chest Radiotherapy: A Report From the Childhood Cancer Survivor Study

Abstract: Purpose Little is known about the breast cancer risk among childhood cancer survivors who did not receive chest radiotherapy. We sought to determine the magnitude of risk and associated risk factors for breast cancer among these women. Patients and Methods We evaluated cumulative breast cancer risk in 3,768 female childhood cancer survivors without a history of chest radiotherapy who were participants in the Childhood Cancer Survivor Study. Results With median follow up of 25.5 years (range, 8 to 39 years), 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
105
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 46 publications
(16 reference statements)
11
105
1
Order By: Relevance
“…Note that in a recent study in childhood cancer survivors not treated with chest irradiation, Henderson and coworkers could not demonstrate a protective effect of ovarian irradiation or alkylating agent chemotherapy on secondary breast cancer risk (Henderson et al 2015). This indicates that gonadotoxic treatment only protects for radiationinduced breast cancer development.…”
Section: :6mentioning
confidence: 95%
See 4 more Smart Citations
“…Note that in a recent study in childhood cancer survivors not treated with chest irradiation, Henderson and coworkers could not demonstrate a protective effect of ovarian irradiation or alkylating agent chemotherapy on secondary breast cancer risk (Henderson et al 2015). This indicates that gonadotoxic treatment only protects for radiationinduced breast cancer development.…”
Section: :6mentioning
confidence: 95%
“…The increased risk for secondary breast cancer in survivors of sarcoma might also be partly related to genetic factors. Data from the Childhood Cancer Survivor Study demonstrated an increased standardized incidence ratio for secondary breast cancer in sarcoma survivors not treated with chest irradiation (5.3 (95% CI: 3.6-7.8)) (Henderson et al 2015). In addition, a positive family history for sarcoma was associated with an increased secondary breast cancer risk (RR 5.3 (95% CI: 1.3-21.5)) (Kenney et al 2004).…”
Section: Primary Cancer Diagnosis and Secondary Breast Cancer Riskmentioning
confidence: 99%
See 3 more Smart Citations